Numerical investigation on the dynamic response of underground tunnel subjected to oil–gas explosion - Chengjun Yue; Li Chen; Qianping Ran; Rui Yin; Ruizhi Xu; Rongzheng Xu (Tunnelling and Underground Space Technology, 2026)

Neoproterozoic mafic complex in the Bikou microblock on the northwestern Yangtze Block: Implications for mantle source and tectonic evolution - Li Qin; Xianzhi Pei; Ruibao Li; Lei Pei; Chengjun Liu; Zuochen Li; Shaowei Zhao; Feng Gao (Lithos, 2026)

Distribution and linkage of microplastics across a sea ice-linked environment in the northwestern Arctic - Haiyan Yang; Jinfeng Ding; Wei Cao; Jingxi Li; Fenghua Jiang; Zhibo Lu; Chengjun Sun (Environmental Pollution, 2026)

Cobalt-doped cotton-derived carbon for enhancing the performance of antimony-removing microbial electrolysis cells - Leyi Chen; Haowen He; Jiayuan Huang; Haifeng Cheng; Chengjun Guo; Xing Chen; Xing Lu; Kengqiang Zhong; Jingyi Wang; Jiaqian Zhang; Meng Li; Lei Huang; et al. (Journal of Water Process Engineering, 2026)

A-site magnesium regulation for defect-optimized perovskite oxides toward efficient and durable alkaline oxygen evolution - Xintong Lv; Kaitao Li; Chengjun Xie; Zijun Xu; Feifei Dong; Yufei Ma; Zhan Lin (Fuel, 2026)

Electrostatic field modulation of beef quality and bacterial community succession under constant or fluctuating temperature storage - Su Wang; Debao Wang; Dongmei Leng; Chengjun Min; Yuxia Qi; Chengli Hou; Xin Li; Yueyu Bai; Dequan Zhang (Food Research International, 2026)

Formation and application of soybean protein amyloid fibril-dextran-epigallocatechin gallate nanoparticles for interfacial engineering of lycopene-loaded Pickering emulsions - Changling Wu; Jie Hou; David Julian McClements; Li Li; Zhaogui Chen; Chengjun Liao; Kaixi Chen; Guangbiao Yan; Hao Hu; Guanyu Fang; Zhiping He; Xingquan Liu; et al. (Food Chemistry, 2026)

Nanofiber ionic bridge framed quasi-solid polymer electrolyte with nanocellulose and PAF for improved low-temperature lithium battery - Jiayi Luo; Shenyuan Li; Yangyang Yu; Chengjun Song; Zhaoyan Sun; Baijun Liu; Wei Hu (Chemical Engineering Journal, 2026)

Evolution of cracks in red-bed mudstone under the coupling of drying-wetting cycle and temperature: From microscopic mechanism to a kinetic model - Guodong Zhang; Sixiang Ling; Chengjun Xiao; Hongwei Liu; Xiaoning Li; Rui Deng; Xiyong Wu (Engineering Geology, 2026)

Assessing the heavy metal(loid) pollution risk potential in Chinese farmland soils: A spatially explicit and multi-source integrated framework - Rongguang Shi; Ye Qiang; Chengjun Chu; Bin Li; Yang Xiao; Nannan Zhang; Yang Guan (Environmental Impact Assessment Review, 2026)

Homogeneous integrated design of polyurethane-based hydrogel electrolytes and electrodes for stretchable supercapacitor - Qingkun Tang; Chengjun Yu; Zuyun Chen; Sisi Yang; Jianxin Tang; Yanqing Li; Songshan Zeng; Xiaoyuan Yu (Chemical Engineering Journal, 2026)

Spatial heterogeneity, source apportionment and ecological risks of trace metal(loid)s in lakes across China - Xue Li; Weijie Yao; Hui Zeng; Xuan Hou; Bin Wang; Xing Yang; Chengjun Ge; Hailong Zhou; Jiwei Luo; Xueqiang Lu (Journal of Hazardous Materials, 2026)

Hydrodynamic performance of a wide–flat ship fitted with dual U-tube anti-rolling tanks in beam seas - Mingsheng Xiahou; Haibin Zhang; Yanwu Tao; Chengjun Li; Deqing Yang (Ocean Engineering, 2026)

Comparison of quality differences in Gastrodia elata wines fermented with different Saccharomyces cerevisiae and potential for sleep improvement in S. cerevisiae SY G. elata fermented wine - Zhiqiang Yi; Weizhong Hu; Huiying Li; Shuxin Zhou; Chengjun Jing; Quang D. Nguyen; Szilárd Kun; Szandra Klátyik; Zhirong Wang; Jianquan Kan; Muying Du (Food Bioscience, 2026)

Uncovering the interaction between surface water heavy metal pollution and industry-induced pressures in Chinese cities - Yang Guan; Ye Qiang; Chengjun Chu; Bin Li; Yang Xiao; Nannan Zhang (Journal of Cleaner Production, 2026)

A critical review of microbial electrochemical systems for uranium remediation: Bioelectrochemical reduction, resource recovery, and sustainability considerations - Jingyi Wang; Ziyin Xia; Liyao Zeng; Leyi Chen; Yiming Jiang; Guanzhen Chen; Chengjun Guo; Jiaqian Zhang; Weiquan Deng; Chenxi Li; Meng Li; Hongguo Zhang (Journal of Environmental Chemical Engineering, 2026)

CYP4G paralog divergence underlies pest resilience to insecticides and warming climate - Huiling Zhou; Shuyan Feng; Meiqi Chen; Meiqian Zhang; Yusi Li; Chengjun Li; Bin Li (Insect Biochemistry and Molecular Biology, 2026)

Physics-based digital twin system for artificial ground freezing: implementation in Bangkok tunnel rehabilitation - Jie Zhou; Chengjun Liu; Chao Ban; Zhenming Shi; Hsinming Shang; Huade Zhou; Zeyao Li (Tunnelling and Underground Space Technology, 2026)

The photo-release of dissolved organic matter from soil-derived sources: An insight into the impact of acid mine drainage - Lezhang Wei; Fangqing Li; Yu Liu; Qihang Wu; Chengjun Zhang; Xuexia Huang; Dinggui Luo; Juan Liu; Tangfu Xiao (Journal of Environmental Sciences, 2026)

High temperature bending sodium heat pipe steam flow field and heat transfer impact analysis - Cheng Xiongwei; Duan Chengjun; Zhang Siwei; Jiang Hualei; Li Taosheng (Annals of Nuclear Energy, 2026)

Early Devonian alkaline volcanism in the North Qaidam, NW China: Insights into the Proto- to Paleo-Tethys tectonic transition - Mao Wang; Xianzhi Pei; Lei Pei; Zuochen Li; Chengjun Liu; Lili Xu; Ruibao Li; Li Qin; Xiao Wang; Nan Hu; Hao Lin (Journal of Asian Earth Sciences, 2026)

Long-term natural photodegradation of plastic films enhances the molecular complexity of plastic-derived dissolved organic matter - Derong Zhang; Jiwei Luo; Xue Li; Dongming Wu; Yanhai Xie; Hui Zeng; Hui Deng; Qingmian Chen; Chengjun Ge; Ying Zhang (Water Research, 2026)

Tonian intra-oceanic subduction initiation at the northwestern Yangtze Block: Evidence from forearc ophiolite fragments in the Bikou microblock - Li Qin; Xianzhi Pei; Ruibao Li; Lei Pei; Chengjun Liu; Zuochen Li; Shaowei Zhao; Feng Gao (Precambrian Research, 2026)

Multi-stage tectono-magmatic evolution of the Proto-Tethys Ocean: Constraints from Mid-Paleozoic granitoids in the East Kunlun-North Qaidam orogenic belt - Mao Wang; Xianzhi Pei; Lei Pei; Ruibao Li; Zuochen Li; Chengjun Liu; Youxin Chen; Nan Hu; Li Qin; Xiao Wang (Gondwana Research, 2026)

Hierarchical dual-crosslinked hydrogel electrolyte with quaternary ammonium and nanofiber reinforcement for durable and flexible zinc-ion batteries - Jiahui Li; Yaxin Wang; Chengxu Wang; Hao Wu; Sheng Li; Jing Ma; Jian Ni; Zhonglong Zhao; Xiaofang Jia; Fuhua Hou; Yanlai Wang; Chengjun Zhu; et al. (Chemical Engineering Journal, 2026)

Livestock-induced changes in soil properties and microbial dominance determine soil microbial diversity in a conifer forest - Fan Fan; Jiangling Zhu; Kai Dong; Suhui Ma; Chengjun Ji; Zhiyao Tang; Shaopeng Wang; Xiaoli Shen; Sheng Li; Jingyun Fang (Soil Ecology Letters, 2026)

Research on the explosion mechanism of gasoline–air mixture in duct considering the distribution of gas cloud and load oscillation - Chengjun Yue; Li Chen; Qianping Ran; Rui Yin; Ruizhi Xu; Rongzheng Xu (Process Safety and Environmental Protection, 2026)

A unified density-aware network for stored-grain pest detection with intelligent risk assessment - Long Chen; Rui Li; Chengjun Xie; Peng Chen; Jie Zhang; Jianming Du; Hongbo Chen; Runsheng Qi; Jiahui Sun (Journal of Stored Products Research, 2026)

Targeted control of beef spoilage: Integrating slaughter-source tracking with packaging-temperature hurdles for precision preservation - Jiarui Li; Dequan Zhang; Ming Tian; Chengjun Min; Debao Wang; Xin Li; Xiaotong Sun; Yanan Tang; Yuxia Qi; Chengli Hou (Food Research International, 2026)

Geometric-semantic enhanced selective Transformer for point cloud registration - Chengjun Wang; Zhen Zheng; Bingting Zha; Haojie Li; Chenyoushi Xu (International Journal of Remote Sensing, 2025)

Overcoming uranium re-dissociation in microbial electrolysis cells: Hydrogen-bond mediated reduction mechanisms in sulfate-reducing bacteria systems - Leyi Chen; Yuchen Yang; Kengqiang Zhong; Xing Lu; Haowen He; Xing Chen; Luoyi Han; Chengjun Guo; Meng Li; Lei Huang; Jia Yan; Diyun Chen; et al. (Chemical Engineering Journal, 2025)

Distribution characteristics of black carbon in Taihu Lake sediments and their effects on microorganisms - Yan Li; Hang Su; Ke Liu; Chengjun Ge; Qingkun Wang; Xinyu Cheng; Jiang Jiang (Environmental Research, 2025)

Cultivated soil environmental risks from key polluting industrial enterprises: An assessment in China - Yang Guan; Ye Qiang; Bin Li; Yang Xiao; Nannan Zhang; Chengjun Chu (Journal of Cleaner Production, 2025)

Harnessing nanomaterial-driven electron transfer for enhanced uranium recovery and toxicity mitigation in bioelectrochemical systems - Meng Li; Leyi Chen; Kengqiang Zhong; Haowen He; Xing Chen; Xing Lu; Chengjun Guo; Luoyi Han; Ziyin Xia; Chenxi Li; Jingyi Wang; Wei Han; et al. (Bioresource Technology, 2025)

Estimation of Genetic Parameters for Hypoxia Tolerance in the Pacific Oyster, Crassostrea gigas - Mengmeng Xu; Ben Yang; Xiaojie Han; Deqi Sun; Chao Guo; Chengjun Zhi; Qi Li; Shikai Liu (Journal of Ocean University of China, 2025)

Neural Network-Based Ship Power Load Forecasting - Haozheng Liu; Chengjun Qiu; Wei Qu; Wei He; Yuan Zhuang; Puze Li; Huili Hao; Wenhao Wang; Zizi Zhao; Jiahua Su (Journal of Marine Science and Engineering, 2025)
This study combines an experimental semi-physical simulation model of an electric propulsion tugboat with four different neural networks to create a real-time simulation model for forecasting total power loads with small samples. The results of repeated experiments demonstrate that the BP neural network effectively forecasts the power load. Subsequently, addressing the limitations of traditional BP neural networks, an optimization approach employing an enhanced particle swarm algorithm and attention mechanism was developed, thereby improving the model’s prediction accuracy and robustness. The experiment shows that the improved prediction model achieves an R2 value of 97.42%, demonstrating its effectiveness in forecasting changes in the short-term power load of ships as parameters change. In actual operation, ships can allocate power reasonably and in a timely manner according to the load forecast results, thereby improving the efficiency of the power grid.

Preparation and evaluation of licochalcone A - integrated casein-pectin nanodelivery system: Insights into its gastrointestinal digestibility and bioavailability - Mei Li; Shuang Yang; Huixiang Yi; Ziying Wang; Bo Xu; Gang Li; Chengjun Ma; Chengshan Yuan; Zhenhua Wang (Food Chemistry, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

5-Hydroxytryptamine mediated 5-HTR4-ILP axis orchestrates glucose utilization and glycogen storage in the Pacific oyster (Crassostrea gigas) - Liting Ren; Ben Yang; Mengmeng Xu; Chengjun Zhi; Qi Li; Shikai Liu (Food Bioscience, 2025)

Dissolved organic matter derived from long-term photodegradation of plastics alters microbial methane conversion in mangrove sediments - Minmin Wang; Leiqian Ma; Derong Zhang; Fan Yang; Xing Yang; Bin Wang; Xue Li; Chengjun Ge; Jiwei Luo; Ying Zhang (Bioresource Technology, 2025)

Autochthonous DOM governs the occurrence and methylation of mercury-containing nanoparticles in urban river water: An integrated study of field investigations and laboratory experiments - Jin Zhang; Pei Lei; Huan Zhong; Nan Zou; Martin Tsz-Ki Tsui; Carl P.J. Mitchell; Chengjun Li; Weiping Cai; Han Meng; Huan He; Fei Dang (Journal of Hazardous Materials, 2025)

Advances in sulfate-reducing bacteria-driven bioelectrolysis: mechanisms and applications in microbial electrolysis cell technology - Chenxi Li; Yuchen Xie; Jingyi Wang; Chengjun Guo; Luoyi Han; Ziyin Xia; Zijian Zhang; Junhe Wang; Meng Li; Wei Han; Lei Huang; Jia Yan; et al. (Environmental Research, 2025)

Occurrence, hydrolysis and photodegradation of phthalate esters in urban atmospheric aqueous aerosol in Wuhan City - Xinyue Zhao; Siyu Liu; Lina Wang; Li Yang; Jun He; Chengjun Wang (Environmental Pollution, 2025)

Optimizing performance and stability in textured 2 T perovskite/silicon tandem photovoltaic devices through self-assembled monolayer-mediated doping strategies - Rui Li; Jungan Wang; Huiwei Du; Chenghao Song; Haochen Zhang; Menglei Xu; Peiting Zheng; Xinyu Zhang; Jie Yang; Chengjun Gu; Qin Zou; Jingji Zhang; et al. (Chemical Engineering Journal, 2025)

Evolution and innovation of the metazoan burrowing behaviour from Ediacaran-Cambrian transition, eastern Yunnan - Da Li; Man Li; Yongan Qi; Guochun Zhao; Jian Fu; Fuqiang Guo; Chengjun Zhang; Jianyu Guan; Shishan Zhang (Precambrian Research, 2025)

Comprehensive review on in vitro bioaccessibility of mercury in various foodstuffs - Yu Gong; Chengjun Li; Fei He; Feng Ge; Yongming Ju; Huan Zhong; Weixin Li (Journal of Hazardous Materials, 2025)

Mechanism of improvement of the power conversion efficiency of Cu2ZnSn(S, Se)4 solar cells through changing Ag and Cd co-doping form from uniform to non-uniform - Mengge Li; Ding Ma; Bin Yao; Yongfeng Li; Zhanhui Ding; Chunkai Wang; Hongmei Luan; Chengjun Zhu (Chemical Engineering Journal, 2025)

Fast decomposition of typical endocrine disturbing compounds in microdroplets under sunlight irradiation in the presence of ozone - Siyu Liu; Xinyue Zhao; Yaobin Ding; Lina Wang; Yiyang Li; Jun He; Chengjun Wang (Chemosphere, 2025)

Sustainable nanofiber films based on polylactic acid/modified cellulose nanocrystals containing various types of polyphenols, exhibiting antioxidant activity and high stability - Chaoqiao Zhu; Qingfeng Yang; Ming Tian; Wei Yang; Chengjun Min; Simin Fan; Debao Wang; Xin Li; Dequan Zhang; Chengli Hou (Food Chemistry, 2025)

Chemical and field-effect passivation coupling for performance enhancement of inverted wide-bandgap perovskite solar cells - Jiali Wei; Xin Wang; Kai Wu; Zhuyou Liu; Jingwei Guo; Haoran Yang; Tiantian Li; Chengjun Zhu; Fuhua Hou (Chemical Engineering Journal, 2025)

Synergistic optimization of bulk defects and back contact in Cu2ZnSn(S,Se)4 solar cells via inducing the heavy-rare-earth erbium ions - Lulu Bai; Yanchun Yang; Guonan Cui; Rui Wang; Zhihui Gong; Shuyu Li; Yongjun Cao; Chengjun Zhu (Chemical Engineering Journal, 2025)

Genetic Basis of Low-Salinity Tolerance in the Pacific Oyster (Crassostrea gigas) as Revealed by Estimation of Genetic Parameters and Genome-Wide Association Study - Xiaojie Han; Ben Yang; Chao Guo; Mengmeng Xu; Deqi Sun; Chengjun Zhi; Qi Li; Shikai Liu (Marine Biotechnology, 2025)

Low-temperature catalytic oxidation of toluene using CeO2@MIL-101(Fe): Stability against water and SO2 - David Murindababisha; Abubakar Yusuf; Kien-Woh Kow; Yong Sun; Run Pan; Yong Ren; George Zheng Chen; Jianrong Li; Chengjun Wang; Jun He (Process Safety and Environmental Protection, 2025)

A density-point network for dense tiny stored grain pest counting - Runsheng Qi; Rui Li; Jie Zhang; Yi Xia; Jianming Du; Jiahui Sun; Long chen; Chengjun Xie; Hui Zhang; Guangyu Li (Journal of Stored Products Research, 2025)

Interface adsorption characteristics of microplastics on multiple morphological arsenic compounds - Di Zhang; Jingxi Li; Chengjun Sun; Corry Yanti Manullang; Jiaxuan Yin; Wei Cao; Fenghua Jiang (Journal of Hazardous Materials, 2025)

Claudin-11 plays a pivotal role in the clathrin-mediated endocytosis of influenza A virus - Xiaofei Yu; Zixin Ni; Yifan Wang; Jingfei Wang; Guohua Deng; Jianzhong Shi; Huihui Kong; Yongping Jiang; Guobin Tian; Chengjun Li; Yoshihiro Kawaoka; Hualan Chen; et al. (Science China Life Sciences, 2025)

Detachment fault system in the Zedang ophiolite of southern Tibet: New insights into the evolution of the neo-Tethys ocean - Yuan Li; Ruibao Li; Chengjun Liu; Jian Zhang; Duoji Ciren; Xiao Zhou; Zhenkai He; Jingsui Yang (Journal of Asian Earth Sciences, 2025)

Field Experiments and a Meta‐Analysis Reveal a Minor Influence of Nitrogen Addition on Phosphorus Fractions in Forests - Qingshui Yu; Xiaofeng Ni; Frank Hagedorn; Josep Penuelas; Jordi Sardans; Mai‐He Li; Suhui Ma; Jianxiao Zhu; Di Tian; Chengyang Zheng; Jiangling Zhu; Chengjun Ji; et al. (Global Change Biology, 2025)
Anthropogenic nitrogen (N) inputs can significantly impact nutrient cycling and ecosystem functioning in terrestrial ecosystems. However, the effects of N addition on phosphorus (P) cycling processes in forest ecosystems remain unclear. In this study, we combined data from a long‐term (11‐year) N addition experiment across seven different forests ranging from temperate to tropical biomes, with a global meta‐analysis from 88 relevant publications, to investigate the responses of P cycling‐related variables to N inputs in forest ecosystems. We found that N addition had little effect on most P cycling‐related variables (e.g., leaf P, soil total P, soil available P, soil P fractions, and microbial biomass P) across the studied forest ecosystems. The meta‐analysis highlighted that N‐induced changes in P cycling were highly variable. Only a few variables, such as the leaf P concentration and the activity of soil acid phosphatase, presented significant responses to N addition and changed with climatic zone and the amount and duration of N inputs. Our study suggests that P cycling processes in forest ecosystems remain largely unaffected by N inputs. Our findings contribute to a better understanding and prediction of biogeochemical cycles in the context of N deposition related to anthropogenic activities and global climate change.

Interlinked water and sediment microplastics in the Laizhou Bay of China - Hong Chen; Fenghua Jiang; Jingxi Li; Wei Cao; Di Zhang; Futao Zhang; Shiliang Wang; Chengjun Sun (Journal of Oceanology and Limnology, 2025)

Soil nematode diversity depends on understory plant species richness in a subalpine forest - Suhui Ma; Yangang Li; Fan Fan; Wenjing Fang; Qiong Cai; Xinyu Xiong; Zhiming Zhang; Jiangling Zhu; Chengjun Ji (Applied Soil Ecology, 2025)

Determination of alkali metal elements in solid biomass fuel by laser-induced breakdown spectroscopy: Analysis and reduction of chemical matrix effects - Chengjun Li; Zhimin Lu; Jinzheng Chen; Ziyu Yu; Qi Yang; Huaiqing Qin; Xiwen Xing; Qingxiang Ma; Shunchun Yao (Analytica Chimica Acta, 2025)

CPTU-Based Offshore Wind Monopile Rigid Bearing Mechanism Analysis - Jie Zhou; Renjie Gu; Panpan Shen; Chengjun Liu; Zeyao Li; Kefan Zhu; Zhenming Shi (Journal of Marine Science and Engineering, 2025)
With the development of the offshore wind industry in China, the amount of offshore wind turbines has increased rapidly. Large-diameter steel monopile foundations of offshore wind turbines have been widely adopted in China with lots of marine clay located. However, the conventional offshore wind monopile bearing capacity prediction from the American Petroleum Institute (API) based on the small-diameter flexible pile field test is inaccurate with the rigid mechanism of large-diameter monopile causing economically loss. The piezocone penetration test (CPTU) is a common marine in situ test to exactly acquire soil parameters. Therefore, a CPTU-based offshore wind monopile rigid mechanism inference method is proposed. A creative numerical offshore wind power monopile and CPTU combined model is established through COMSOL. A self-compiling parameter function is applied to soil modeling and an innovative mobile boundary function is created to simulate CPTU penetration. Through the model, real-time CPTU data can be acquired when monopile is applied with different horizontal loads. The peripile soil stress change can be timely detected by CPTU. Through CPTU data, the monopile rigid bearing mechanism is verified. A rigid rotation center is found at the 60% point of the inserted monopile. The method is an important foundation for the next step of monopile bearing capacity research.

Microplastic occurrence and hydrodynamic-sedimentary driving effects in the Bohai Strait region of China - Long Zhou; Chengjun Sun; Jingxi Li; Chang Zhao; Jinfeng Ding; Wei Cao; Fenghua Jiang (Science of The Total Environment, 2025)

C-type lectin 9 participates in the immune response, development and reproduction of Tribolium castaneum - Chengjun Li; Huayi Ai; Biao Zhang; Xiaoqiao Huang; Bin Li (Pesticide Biochemistry and Physiology, 2025)

Achieving high-efficiency Cu2ZnSn(S,Se)4 solar cells by Ag doping in Cu2ZnSn(S,Se)4 and substituting annealed In0.01Cd0.99S for CdS - Ding Ma; Mengge Li; Bin Yao; Yongfeng Li; Zhanhui Ding; Hongmei Luan; Chengjun Zhu; Jiayong Zhang; Chunkai Wang (Chemical Engineering Journal, 2025)

SnS-induced element diffusion Simultaneous optimization of interface and bulk defects in High-Efficiency CZTSSe solar cells - Chenjun Yang; Letu Siqin; Yutian Wang; Yufei Li; Wenbo Li; Shuyu Li; Ruijian Liu; Hongmei Luan; Chengjun Zhu (Chemical Engineering Journal, 2025)

Chronic exposure to hexavalent chromium induces esophageal tumorigenesis via activating the Notch signaling pathway - Yilin Zhu; Fanrong Liu; Lei Liu; Jinfu Wang; Fengyuan Gao; Lan Ye; Honglei Wu; Chengjun Zhou; Guimei Lin; Xiaogang Zhao; Peichao Li (Journal of Zhejiang University-SCIENCE B, 2025)

Erratum to: The effect of typical seawater cations on the adhesion of mussel protein Mefp-1 based on dissipative quartz crystal microbalance - Futao Zhang; Chengjun Sun; Linqing Xie; Fuqian Li; Fenghua Jiang; Jingxi Li (Journal of Oceanology and Limnology, 2025)

The effect of typical seawater cations on the adhesion of mussel protein Mefp-1 based on dissipative quartz crystal microbalance - Futao Zhang; Chengjun Sun; Linqing Xie; Fuqian Li; Fenghua Jiang; Jingxi Li (Journal of Oceanology and Limnology, 2025)

Abundance of microplastics and its ecological risk assessment in coral reef regions of Peninsular Malaysia - Kok Ping Lim; Chengjun Sun; Sumiani Yusoff; Jinfeng Ding; Kar Hoe Loh; Jingxi Li; Phaik Eem Lim (Marine Pollution Bulletin, 2024)

Coseismic surface deformation and source mechanism of the 2023 Ms 6.2 Jishishan earthquake, northeastern Tibetan Plateau - Peng Chen; Siqi Shu; Zhonghai Wu; Tao Wang; Chengjun Feng; Jiamei Liu; Shuai Zhang; Haojie Wang; Kun Li (Journal of Structural Geology, 2024)

High-resolution mapping of grassland canopy cover in China through the integration of extensive drone imagery and satellite data - Tianyu Hu; Mengqi Cao; Xiaoxia Zhao; Xiaoqiang Liu; Zhonghua Liu; Liangyun Liu; Zhenying Huang; Shengli Tao; Zhiyao Tang; Yanpei Guo; Chengjun Ji; Chengyang Zheng; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Thermal performance of multifunctional louver window integrated phase change material and spherical louver - Dong Li; Yanjiao Duan; Chengjun Zhang; Wanyu Hu; Xinpeng Yang; Qiang Fu; Müslüm Arıcı; Ruitong Yang; Xueyang Wang (Energy and Buildings, 2024)

CCL2-scavenging nanodecoy hydrogel multi-step remodel monocytes recruitment and macrophages polarization for periodontitis treatment - Yuxiao Wang; Guichun Wang; Jiaxin Li; Maomao Tang; Baoqing Jia; Zixuan Shu; Yang Ding; Chengjun Peng; Shuangying Gui; Jian Guo (Chemical Engineering Journal, 2024)

Correction: Roles of estrogen receptors during sexual reversal in pelodiscus sinensis - Guobin Chen; Tong Zhou; Jizeng Cao; Xiang Li; Chengjun Zhu; Long Wang; Guiwei Zou; Hongwei Liang (Molecular Biology Reports, 2024)

Roles of estrogen receptors during sexual reversal in Pelodiscus sinensis - Guobin Chen; Tong Zhou; Jizeng Cao; Xiang Li; Chengjun Zhu; Long Wang; Guiwei Zou; Hongwei Liang (Molecular Biology Reports, 2024)

Characterizing the soil microbiome to predict mercury risks - Wenli Tang; Chengjun Li; Huan Zhong (Soil Ecology Letters, 2024)

Precipitation nowcasting leveraging spatial correlation feature extraction and deep spatio-temporal fusion network - Wenbin Yu; Yangsong Li; Cheng Fan; Daoyong Fu; Chengjun Zhang; Yadang Chen; Ming Qian; Jie Liu; Gaoping Liu (Earth Science Informatics, 2024)

Optimizing the indoor thermal environment and daylight performance of buildings with PCM glazing - Wanyu Hu; Yanjiao Duan; Dong Li; Chengjun Zhang; Hui Yang; Ruitong Yang (Energy and Buildings, 2024)

Effects of polypropylene films and leached dissolved organic matters on bacterial community structure in mangrove sediments - Jiatong Li; Xue Li; Jiwei Luo; Peng Huang; Chengjun Ge; Xing Yang; Hailong Wang (Science of The Total Environment, 2024)

Empagliflozin attenuates doxorubicin-impaired cardiac contractility by suppressing reactive oxygen species in isolated myocytes - Rong Lin; Xiaodong Peng; Yukun Li; Xuesi Wang; Xinmeng Liu; Xingze Jia; Chengjun Zhang; Nian Liu; Jianzeng Dong (Molecular and Cellular Biochemistry, 2024)

Detrital Zircon Geochronology of Early Triassic Strata in the West Qinling Orogen: Implications for the Tectonic Evolution of the Paleo-Tethyan Ocean - Zuochen Li; Xianzhi Pei; Liyong Wei; Guobing Liang; Meng Wang; Ruibao Li; Lei Pei; Chengjun Liu; Youxin Chen; Feng Gao (Journal of Earth Science, 2024)

Occurrence of microplastics in the Haima cold seep area of the South China Sea - Di Zhang; Jingxi Li; Peng Ju; Wei Cao; Fenghua Jiang; Chengjun Sun (Science of The Total Environment, 2024)

Effectiveness of natural ventilation through single-sided window opening in air-conditioning rooms - Xinyu Liu; Hanqing Wang; Zhengming Li; Jinping Zhao; Chengjun Li; Dong Xie (Energy and Buildings, 2024)

Environmental characteristics of trace metals in seawater from the Ninety East Ridge in the Indian Ocean - Jingxi Li; Di Zhang; Fenghua Jiang; Hong Chen; Wei Cao; Chengjun Sun (Journal of Oceanology and Limnology, 2024)

Mercury supply limits methylmercury production in paddy soils - Huan Zhong; Yao Su; Xinda Wu; Luís Nunes; Chengjun Li; Yunyun Hao; Yu-Rong Liu; Wenli Tang (Science of The Total Environment, 2024)

Origin of granitoids and coeval mafic microgranular enclaves in the East Kunlun Orogen, northern Tibetan Plateau: Insights from petrography, U-Pb geochronology, geochemical and isotope analyses - Guochao Chen; Xianzhi Pei; Ruibao Li; Zuochen Li; Lei Pei; Chengjun Liu; Youxin Chen (Journal of Asian Earth Sciences, 2024)

Life-cycle profiling of cuticular hydrocarbons in the cotton bollworm Helicoverpa armigera (Lepidoptera: Noctuidae) - Chengjun Ma; Yucui Xin; Ruoyao Ni; Mei Li; Xinghui Qiu (Journal of Asia-Pacific Entomology, 2024)

Identification of self-interstitial atoms and vacancies in crystalline materials in atomistic simulation - Jun Wang; Tao Li; Ziwen Fu; Baoqin Fu; Chengjun Gou (Computer Physics Communications, 2024)

A C-type lectin (CTL2) mediated both humoral and cellular immunity against bacterial infection in Tribolium castaneum - Suisui Wang; Shiyuan Miao; Yujie Lu; Chengjun Li; Bin Li (Pesticide Biochemistry and Physiology, 2024)

Insights into the generation of multiple reactive species in UV254/PMS/I− system and their roles for degradation of phenolic and non-phenolic pollutants - Zhen Tian; Yiyang Li; Lina Wang; Rui Xu; Aihua Wei; Jun He; Chengjun Wang (Journal of Water Process Engineering, 2024)

Genomic selection accelerates genetic improvement of resistance to Vibriosis in the Pacific oyster, Crassostrea gigas - Ben Yang; Chengjun Zhi; Pengfei Li; Chengxun Xu; Qi Li; Shikai Liu (Aquaculture, 2024)

Methylmercury photodegradation in paddy water: An overlooked process mitigating methylmercury risks - Huan Zhong; Hangyu Zhou; Yanbin Li; Chengjun Li; Martin Tsz-Ki Tsui; Carl P.J. Mitchell; Yang Zhou; Yanan Yang; Long Chen; Hongqiang Ren; Wenli Tang (Water Research, 2024)

Positive effects of vegetation restoration on the soil properties of post-mining land - Cuihuan Li; Yongkang Ji; Nan Ma; Jing Zhang; Hui Zhang; Chengjun Ji; Jiangling Zhu; Junjiong Shao; Yan Li (Plant and Soil, 2024)

Soil total and available C:N:P stoichiometry among different parent material soil profiles in rubber plantations of Hainan Island, China - Yuzhu Li; Yue Zhao; Xuelian Bao; Hongtu Xie; Xiaotao Lü; Yangang Fu; Shixin Tang; Chengjun Ge; Chao Liang (Geoderma Regional, 2024)

A layered sodium-ion host O3-NaFe0.5Ti0.5O2 enables Na-free cathodes through offering extractable Na-ions - Qingyang Song; Peng Shi; Zhiqiang Guo; Peng Zhang; Yuanhang Li; Xiaohui Rong; Xiaoyan Wu; Shuyin Xu; Huican Mao; Yingchun Lyu; Chengjun Zhu (Chemical Engineering Journal, 2024)

M6PR interacts with the HA2 subunit of influenza A virus to facilitate the fusion of viral and endosomal membranes - Yuzhen Hu; Li Jiang; Guangwen Wang; Yangming Song; Zhibo Shan; Xuyuan Wang; Guohua Deng; Jianzhong Shi; Guobin Tian; Xianying Zeng; Liling Liu; Hualan Chen; et al. (Science China Life Sciences, 2024)

Interplays between plants and environmental factors determine pullout resistance on different revegetated slopes in mining areas - Zhang Chen; Oumeng Qiao; Yong Liu; Keming Ma; Huiping Song; Chengjun Li (Journal of Environmental Management, 2024)

Spatial distribution and seasonal variation of trace hazardous elements contamination in the coastal environment - Ramamoorthy Ayyamperumal; Balasubramanian Muthusamy; Xiaozhong Huang; Zhang Chengjun; Nusrat Nazir; Fengjie Li (Environmental Research, 2024)

Quantifying climate variation and associated regional air pollution in southern India using Google Earth Engine - Ramamoorthy Ayyamperumal; Abhishek Banerjee; Zhenhua Zhang; Nusrat Nazir; Fengjie Li; Chengjun Zhang; Xiaozhong Huang (Science of The Total Environment, 2024)

Distribution, sources and ecological risks of per- and polyfluoroalkyl substances in overlying water and sediment from the mangrove ecosystem in Hainan Island, China - Guoliang Ren; Like Chen; Jinluo Fan; Shuailing Hou; Junnan Chen; Hui Deng; Jiwei Luo; Peng Huang; Yuanyuan Zhao; Jiatong Li; Dan Feng; Chengjun Ge; et al. (Science of The Total Environment, 2024)

Integrated microbiota and multi-omics analysis reveal the differential responses of earthworm to conventional and biodegradable microplastics in soil under biogas slurry irrigation - Yuanyuan Zhao; Huiting Jia; Hui Deng; Chengjun Ge; Wenzhe Xing; Huamei Yu; Jiatong Li (Science of The Total Environment, 2024)

Facile synthesis of multi-layer Co(OH)2/CeO2-g-C3N4 ternary synergistic heterostructure for efficient photocatalytic oxidation of NO under visible light - Zhiyu Xiao; Hainam Do; Abubakar Yusuf; Hongpeng Jia; Haolun Ma; Shanshan Jiang; Jianrong Li; Yong Sun; Chengjun Wang; Yong Ren; George Zheng Chen; Jun He (Journal of Hazardous Materials, 2024)

Differential evolution with alternation between steady monopoly and transient competition of mutation strategies - Chenxi Ye; Chengjun Li; Yang Li; Yufei Sun; Wenxuan Yang; Mingyuan Bai; Xuanyu Zhu; Jinghan Hu; Tingzi Chi; Hongbo Zhu; Luqi He (Swarm and Evolutionary Computation, 2023)

Preparation of leaf protoplasts from Populus (Populus × xiaohei T. S. Hwang et Liang) and establishment of transient expression system - Chengjun Yang; Ruiqiang Yu; Jinbo Li; Kai Wang; Guanjun Liu (Journal of Plant Physiology, 2023)

Experimental study on gas explosions of methane-air mixtures in a full-scale residence building - Chengjun Yue; Li Chen; Zhan Li; Yuanchao Mao; Xiaohu Yao (Fuel, 2023)

Regulation of electrical properties via ferroelectric polarization for high performance Sb2Te3 thermoelectric thin films - Boyu Yang; Yubo Luo; Chengjun Li; Wang Li; Chengwei Sun; Zheng Ma; Yongxin Qian; Xianwei Zeng; Yingchao Wei; Haiqiang Liu; Dan Zhang; Xin Li; et al. (Chemical Engineering Journal, 2023)

Environmental hazard assessment and metal contamination in coastal sediments - Ramamoorthy Ayyamperumal; Kajal Kumari; M Suresh Gandhi; Xiaozhong Huang; Zhang Chengjun; Nusrat Nazir; Fengjie Li; Priyanko Das (Chemosphere, 2023)

Integrated microbiome and multi-omics analysis reveal the molecular mechanisms of Eisenia fetida in response to biochar-derived dissolved and particulate matters - Huiting Jia; Yuanyuan Zhao; Hui Deng; Huamei Yu; Chengjun Ge; Jiatong Li (Journal of Hazardous Materials, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

A Review of Microplastics in China Marine Waters - Fenglei Gao; Jingxi Li; Jun Hu; Xianguo Li; Chengjun Sun (Journal of Ocean University of China, 2023)

Wnt10a downregulation contributes to MEHP-induced disruption of self-renewal and differentiation balance and proliferation inhibition in GC-1 cells: Insights from multiple transcriptomic profiling - Yifan Hong; Xiazhu Zhou; Qi Li; Jing Chen; Yuexin Wei; Siyuan Wang; Xiangqin Zheng; Jie Zhao; Chengjun Yu; Jun Pei; Jie Zhang; Chunlan Long; et al. (Environmental Pollution, 2023)

Coupled anaerobic methane oxidation and metal reduction in soil under elevated CO 2 - Chenchao Xu; Naifang Zhang; Kaihang Zhang; Shuyao Li; Qing Xia; Jing Xiao; Maojun Liang; Weilei Lei; Junpan He; Gaiping Chen; Chengjun Ge; Xunhua Zheng; et al. (Global Change Biology, 2023)
Continued current emissions of carbon dioxide (CO 2 ) and methane (CH 4 ) by human activities will increase global atmospheric CO 2 and CH 4 concentrations and surface temperature significantly. Fields of paddy rice, the most important form of anthropogenic wetlands, account for about 9% of anthropogenic sources of CH 4 . Elevated atmospheric CO 2 may enhance CH 4 production in rice paddies, potentially reinforcing the increase in atmospheric CH 4 . However, what is not known is whether and how elevated CO 2 influences CH 4 consumption under anoxic soil conditions in rice paddies, as the net emission of CH 4 is a balance of methanogenesis and methanotrophy. In this study, we used a long‐term free‐air CO 2 enrichment experiment to examine the impact of elevated CO 2 on the transformation of CH 4 in a paddy rice agroecosystem. We demonstrate that elevated CO 2 substantially increased anaerobic oxidation of methane (AOM) coupled to manganese and/or iron oxides reduction in the calcareous paddy soil. We further show that elevated CO 2 may stimulate the growth and metabolism of Candidatus Methanoperedens nitroreducens , which is actively involved in catalyzing AOM when coupled to metal reduction, mainly through enhancing the availability of soil CH 4 . These findings suggest that a thorough evaluation of climate‐carbon cycle feedbacks may need to consider the coupling of methane and metal cycles in natural and agricultural wetlands under future climate change scenarios.

Experiments and machine learning-based modeling for haloacetic acids rejection by nanofiltration: Influence of solute properties and operating conditions - Feifei Wang; Weikang Wang; Hongjie Wang; Zilong Zhao; Ting Zhou; Chengjun Jiang; Ji Li; Xiaolei Zhang; Tianzhe Liang; Wenyi Dong (Science of The Total Environment, 2023)

Benefited wastewater utilization via configurable, spatialized, and microorganisms-integrated biophotonic systems - Yantong Liu; Longfei Chen; Le Yu; Jiaomeng Zhu; Fang Wang; Fenghua Jiang; Chengjun Sun; Li Zheng; Yi Yang (Chemical Engineering Journal, 2023)

Mercury in wetlands over 60 years: Research progress and emerging trends - Jin Zhang; Chengjun Li; Wenli Tang; Mengjie Wu; Mingying Chen; Huan He; Pei Lei; Huan Zhong (Science of The Total Environment, 2023)

R-loopAtlas: An integrated R-loop resource from 254 plant species sustained by a deep-learning-based tool - Kuan Li; Zhenzhen Wu; Jincong Zhou; Wei Xu; Ling Li; Chao Liu; Wei Li; Chengjun Zhang; Qianwen Sun (Molecular Plant, 2023)

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

Response of earthworms to microplastics in soil under biogas slurry irrigation: Toxicity comparison of conventional and biodegradable microplastics - Yuanyuan Zhao; Huiting Jia; Hui Deng; Wenzhe Xing; Dan Feng; Jiatong Li; Chengjun Ge; Huamei Yu; Ying Zhang; Haiying Chen (Science of The Total Environment, 2023)

Unraveling the joint toxicity of transition-metal dichalcogenides and per- and polyfluoroalkyl substances in aqueous mediums by experimentation, machine learning and molecular dynamics - Guohong Liu; Xiliang Yan; Chengjun Li; Song Hu; Jiachen Yan; Bing Yan (Journal of Hazardous Materials, 2023)

Zn2+ loading as a critical contributor to the circ_0008553-mediated oxidative stress and inflammation in response to PM2.5 exposures - Jingzhou Wang; Jianbo Jia; Dujia Wang; Xiujiao Pan; Haiyan Xiong; Chengjun Li; Yiguo Jiang; Bing Yan (Journal of Environmental Sciences, 2023)

Magmatic response to the closure of the Proto-Tethys Ocean: A case study from the middle Paleozoic granitoids in the Kunlun Orogen, western China - Ruibao Li; Xianzhi Pei; Renjie Zhou; Zuochen Li; Lei Pei; Guochao Chen; Youxin Chen; Chengjun Liu (Journal of Asian Earth Sciences, 2023)

Trash to treasure: Green synthesis of novel Ag2O/Ag2CO3 Z-scheme heterojunctions with highly efficient photocatalytic activities derived from waste mussel shells - Jiazhen Cao; Peng Ju; Zheyang Chen; Kunpeng Dou; Jingxi Li; Peng Zhang; Zuhao Zhu; Chengjun Sun (Chemical Engineering Journal, 2023)

Continued evolution of the Eurasian avian-like H1N1 swine influenza viruses in China - Fei Meng; Yan Chen; Zuchen Song; Qiu Zhong; Yijie Zhang; Chuanling Qiao; Cheng Yan; Huihui Kong; Liling Liu; Chengjun Li; Huanliang Yang; Hualan Chen (Science China Life Sciences, 2023)

Late glacial and Holocene climate in the Kunlun Pass region (northern Tibetan Plateau) inferred from a multi-proxy lake record - Wanyi Zhang; Steffen Mischke; Dominic Hosner; Chengjun Zhang; Birgit Plessen; Huwei Li; Xiaojing Zhang (Quaternary International, 2023)

Reconfigurable modular microbiota systems for efficient and sustainable water treatment - Longfei Chen; Yantong Liu; Pengfu Tian; Le Yu; Fang Wang; Hongshan Xu; Yifan Wang; Wei Li; Li Zheng; Fenghua Jiang; Chengjun Sun; Xuming Zhang; et al. (Chemical Engineering Journal, 2023)

Reaching the Full Potential of Machine Learning in Mitigating Environmental Impacts of Functional Materials - Ying He; Guohong Liu; Chengjun Li; Xiliang Yan (Reviews of Environmental Contamination and Toxicology, 2022)

Petrogenesis and tectonic setting of Early Silurian island-arc-type quartz diorite at the southern margin of the East Kunlun orogenic belt: analysis of the evolution of the Proto-Tethyan Ocean - Zuochen Li; Xianzhi Pei; Ruibao Li; Paul D. Bons; Lei Pei; Youxin Chen; Chengjun Liu; Meng Wang; Shaowei Zhao; Guochao Chen; Hai Zhou; Jie Zhao; et al. (International Journal of Earth Sciences, 2022)

Reply to Comments on “A Scientometric Analysis of Recent Literature on Arsenic Bioaccumulation and Biotransformation in Marine Ecosystems” - Chengjun Li; Huan Zhong; Wei Zhang (Bulletin of Environmental Contamination and Toxicology, 2022)

Dynamic response of the inhomogeneous pavement structure containing a buried fault zone under the moving aircraft loads - Jiawei Wan; Bin Li; Yang Gao; Chengxuan Tan; Chengjun Feng; Peng Zhang (Bulletin of Engineering Geology and the Environment, 2022)

Dietary addition of fermented sorghum distiller’s dried grains with soluble improves carcass traits and meat quality in growing-finishing pigs - Huawei Li; Yehui Duan; Fugui Yin; Qian Zhu; Chengjun Hu; Lingying Wu; Peifeng Xie; Fengna Li; Runxi Cheng; Xiangfeng Kong (Tropical Animal Health and Production, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Upper-Ocean Lateral Heat Transports in the Niño3.4 Region and Their Connection with ENSO - He Zhao; Tongwen Wu; Laurent Z. X. Li; Fanghua Wu; Weihua Jie; Xiangwen Liu; Ronghua Zhang; Chengjun Xie (Journal of Meteorological Research, 2022)

Combined Effects of Microplastics and Benzo[a]pyrene on the Marine Diatom Chaetoceros muelleri - Yuanyuan Su; Huaiyuan Qi; Yipeng Hou; Mengyi Gao; Jie Li; Minggang Cai; Xiaoshan Zhu; Miao Chen; Chengjun Ge; Dongdong Fu; Zezheng Wang; Licheng Peng (Frontiers in Marine Science, 2022)
Microplastics are regarded as ubiquitous pollutants in the ocean and have attracted worldwide concerns. Benzo[a]pyrene (B[a]P), one of typical polycyclic aromatic hydrocarbons (PAHs), is commonly detected in marine environment. Once coexisted, the microplastics and B[a]P may interact with each other and result in combined toxicity to organisms, and these remain to be systematically elucidated. Thus, this study aims to investigate (i) the effects of single micro-sized polystyrene (mPS), polyethylene terephthalate (mPET), and B[a]P on cell growth of Chaetoceros muelleri ; and (ii) the interaction of microplastics and B[a]P, and their combined effects on C. muelleri . The results showed that both single microplastics and B[a]P at a high concentration of 150 μg/L inhibited the growth of C. muelleri . For single treatment of microplastics, stronger inhibition effects on microalgae was caused by mPET than that of mPS, with the highest IR of 25.23 and 11.17%, respectively. This may be attributed to the obvious surface roughness of mPET. By comparison, the combined effects of microplastics and B[a]P significantly inhibited the growth of C. muelleri as compared with the single treatment of B[a]P ( P < 0.05). Synergistic effect was found in the combination of microplastics with B[a]P at high concentrations of 150 μg/L. Interestingly, the antagonistic effect on C. muelleri was observed in the combined treatment of microplastics and B[a]P at low concentrations of 10 μg/L. In addition, the pollutants reduced the content of photosynthetic pigments in microalgal cells. The SOD and MDA content of microalgae increased in the early stage of exposure to pollutants (e.g., Days 1 and 5), but decreased in the later stage (Day 15) compared with the control group. The decreased superoxide dismutase (SOD) and catalase (CAT) activity in single and composite systems may indicate that the antioxidative enzymatic system of microalgae has been inhibited or destroyed. This study will be helpful to further explore the ecological threats of microplastics and PAHs to the marine ecosystem.

Complete genome sequence of a novel mitovirus from the phytopathogenic fungus Fusarium oxysporum - Jing Wang; Chengjun Li; Rui Qiu; Xiaojie Li; Jun Zhao; Jingke Bai; Yuguo Chen; Shujun Li (Archives of Virology, 2021)

Simultaneous 3D Visualization of the Microvascular and Neural Network in Mouse Spinal Cord Using Synchrotron Radiation Micro-Computed Tomography - Liyuan Jiang; Chengjun Li; Miao Li; Xianzhen Yin; Tianding Wu; Chunyue Duan; Yong Cao; Hongbin Lu; Jianzhong Hu (Neuroscience Bulletin, 2021)
Effective methods for visualizing neurovascular morphology are essential for understanding the normal spinal cord and the morphological alterations associated with diseases. However, ideal techniques for simultaneously imaging neurovascular structure in a broad region of a specimen are still lacking. In this study, we combined Golgi staining with angiography and synchrotron radiation micro-computed tomography (SRμCT) to visualize the 3D neurovascular network in the mouse spinal cord. Using our method, the 3D neurons, nerve fibers, and vasculature in a broad region could be visualized in the same image at cellular resolution without destructive sectioning. Besides, we found that the 3D morphology of neurons, nerve fiber tracts, and vasculature visualized by SRμCT were highly consistent with that visualized using the histological method. Moreover, the 3D neurovascular structure could be quantitatively evaluated by the combined methodology. The method shown here will be useful in fundamental neuroscience studies.

Progresses and emerging trends of arsenic research in the past 120 years - Chengjun Li; Jiahui Wang; Bing Yan; Ai-Jun Miao; Huan Zhong; Wei Zhang; Lena Qiying Ma (Critical Reviews in Environmental Science and Technology, 2021)

A combinatorial method to visualize the neuronal network in the mouse spinal cord: combination of a modified Golgi-Cox method and synchrotron radiation micro-computed tomography - Liyuan Jiang; Yong Cao; Xianzhen Yin; Shuangfei Ni; Miao Li; Chengjun Li; Zixiang Luo; Hongbin Lu; Jianzhong Hu (Histochemistry and Cell Biology, 2021)
Exploring the three-dimensional (3D) morphology of neurons is essential to understanding spinal cord function and associated diseases comprehensively. However, 3D imaging of the neuronal network in the broad region of the spinal cord at cellular resolution remains a challenge in the field of neuroscience. In this study, to obtain high-resolution 3D imaging of a detailed neuronal network in the mass of the spinal cord, the combination of synchrotron radiation micro-computed tomography (SRμCT) and the Golgi-cox staining were used. We optimized the Golgi-Cox method (GCM) and developed a modified GCM (M-GCM), which improved background staining, reduced the number of artefacts, and diminished the impact of incomplete vasculature compared to the current GCM. Moreover, we achieved high-resolution 3D imaging of the detailed neuronal network in the spinal cord through the combination of SRμCT and M-GCM. Our results showed that the M-GCM increased the contrast between the neuronal structure and its surrounding extracellular matrix. Compared to the GCM, the M-GCM also diminished the impact of the artefacts and incomplete vasculature on the 3D image. Additionally, the 3D neuronal architecture was successfully quantified using a combination of SRμCT and M-GCM. The SRμCT was shown to be a valuable non-destructive tool for 3D visualization of the neuronal network in the broad 3D region of the spinal cord. Such a combinatorial method will, therefore, transform the presentation of Golgi staining from 2 to 3D, providing significant improvements in the 3D rendering of the neuronal network.

Study on the operational efficiency of prefabricated building industry bases in Western China based on the DEA model - Sunmeng Wang; Chengjun Wang; Wenlong Li; Di Zhao (Arabian Journal of Geosciences, 2021)

Geochemistry and tectonic setting of Middle Ordovician MORB-like basalts in the Kunlun Orogen: implications for a back-arc environment - Ruibao Li; XianZhi Pei; Zuochen Li; Lei Pei; Youxin Chen; Chengjun Liu; Guochao Chen; Keng Feng (Arabian Journal of Geosciences, 2021)

Distribution pattern and geochemical analysis of rare earth elements in deep-ocean sediments - Jingxi Li; Chengjun Sun; Fenghua Jiang; Fenglei Gao; Yifan Zheng (Journal of Oceanology and Limnology, 2021)

Variation of soil nitrate and bacterial diversity along soil profiles in manure disposal maize field and adjacent woodland - Yujia Cai; Ju-Pei Shen; Hong J. Di; Li-Mei Zhang; Chengjun Zhang; Ji-Zheng He (Journal of Soils and Sediments, 2020)

Comparative toxicity of five dispersants to test organisms at different trophic levels: Platymonas helgolandica, Ruditapes philippinarum, and Acinetobacter sp. Tox2 - Zhisong Cui; Xiao Luan; Dandan Li; Qian Li; Limei Shuai; Li Zheng; Chengjun Sun; Gaoge Wang (Environmental Science and Pollution Research, 2020)

Characteristics and main causes of earth fissures in northeastern Beijing Plain, China - Jiawei Wan; Bin Li; Chengxuan Tan; Chengjun Feng; Peng Zhang; Bangshen Qi (Bulletin of Engineering Geology and the Environment, 2020)

Comparison of sedimentary organic carbon loading in the Yap Trench and other marine environments - Dong Li; Jun Zhao; Chenggang Liu; Chengjun Sun; Jianfang Chen; Jianming Pan; Zhengbing Han; Ji Hu (Journal of Oceanology and Limnology, 2020)

A Scientometric Analysis of Recent Literature on Arsenic Bioaccumulation and Biotransformation in Marine Ecosystems - Chengjun Li; Huan Zhong; Wei Zhang (Bulletin of Environmental Contamination and Toxicology, 2020)

Differentiated super-enhancers in lung cancer cells - Xin Li; Chengjun Lu; Qijue Lu; Chunguang Li; Ji Zhu; Tiejun Zhao; Hezhong Chen; Hai Jin (Science China Life Sciences, 2019)

Migration of phthalates from plastic packages to convenience foods and its cumulative health risk assessments - Jinling Yang; Weizhong Song; Xiaojie Wang; Yongxin Li; Jiannan Sun; Weilei Gong; Chengjun Sun (Food Additives & Contaminants Part B-Surveillance, 2019)

The latest tectonic magmatism in the Buqingshan–A’nyemaqen tectonic mélange belt: evidence from zircon U–Pb geochronology of intermediate–basic dikes, northern Tibetan Plateau, China - Zuochen Li; Xianzhi Pei; Ruibao Li; Lei Pei; Youxin Chen; Chengjun Liu; Zhanqing Liu; Guochao Chen; Meng Wang; Shaowei Zhao (Arabian Journal of Geosciences, 2019)

Degradation potential and diversity of oil-degrading bacteria isolated from the sediments of the Jiaozhou Bay, China - Wei Gao; Xiangxing Gao; Tiezhu Mi; Bin Han; Yiran Zhang; Xinzi Li; Xiaofei Yin; Chengjun Sun; Qian Li; Zhisong Cui; Xiao Luan; Zhigang Yu; et al. (Acta Oceanologica Sinica, 2019)

Cambrian (~510 Ma) ophiolites of the East Kunlun orogen, China: A case study from the Acite ophiolitic tectonic mélange - Ruibao Li; XianZhi Pei; Zuochen Li; Lei Pei; Guochao Chen; Bo Wei; Youxin Chen; Chengjun Liu; Meng Wang (International Geology Review, 2018)

Vaccination of poultry successfully eliminated human infection with H7N9 virus in China - Xianying Zeng; Guobin Tian; Jianzhong Shi; Guohua Deng; Chengjun Li; Hualan Chen (Science China Life Sciences, 2018)

Degradation of lipids in seasonal hypoxic seawater under different oxygen saturation - Yunhong He; Chengjun Sun; Wenjuan Li; Gui-Peng Yang; Haibing Ding (Journal of Oceanology and Limnology, 2018)

Identification of drug target candidates of the swine pathogen Actinobacillus pleuropneumoniae by construction of protein–protein interaction network - Siqi Li; Zhipeng Su; Chengjun Zhang; Zhuofei Xu; Xiaoping Chang; Jiawen Zhu; Ran Xiao; Lu Li; Rui Zhou (Genes & Genomics, 2018)

Study on immobilization of marine oil-degrading bacteria by carrier of algae materials - Yiran Zhang; Wei Gao; Faxiang Lin; Bin Han; Changfei He; Qian Li; Xiangxing Gao; Zhisong Cui; Chengjun Sun; Li Zheng (World Journal of Microbiology and Biotechnology, 2018)

Lipid accumulation and CO2 utilization of two marine oil-rich microalgal strains in response to CO2 aeration - Shuai Wang; Li Zheng; Xiaotian Han; Baijuan Yang; Jingxi Li; Chengjun Sun (Acta Oceanologica Sinica, 2018)

Retraction Note to: CXCL12/CXCR4 Axis Upregulates Twist to Induce EMT in Human Glioblastoma - Chengjun Yao; Panpan Li; Huishu Song; Fuxi Song; Yalan Qu; Xiaochen Ma; Ranran Shi; Jinsong Wu (Molecular Neurobiology, 2017)

RETRACTED ARTICLE: CXCL12/CXCR4 Axis Upregulates Twist to Induce EMT in Human Glioblastoma - Chengjun Yao; Panpan Li; Huishu Song; Fuxi Song; Yalan Qu; Xiaochen Ma; Ranran Shi; Jinsong Wu (Molecular Neurobiology, 2016)

Effects of red mud addition on cadmium accumulation in cole (Brassica campestris L.) under high fertilization conditions - Peng Li; Xianjia Peng; Zhaokun Luan; Tongke Zhao; Chengjun Zhang; Baocun Liu (Journal of Soils and Sediments, 2016)

The permafrost carbon inventory on the Tibetan Plateau: a new evaluation using deep sediment cores - Jinzhi Ding; Fei Li; Guibiao Yang; Leiyi Chen; Beibei Zhang; Li Liu; Kai Fang; Shuqi Qin; Yongliang Chen; Yunfeng Peng; Chengjun Ji; Honglin He; et al. (Global Change Biology, 2016)
The permafrost organic carbon ( OC ) stock is of global significance because of its large pool size and the potential positive feedback to climate warming. However, due to the lack of systematic field observations and appropriate upscaling methodologies, substantial uncertainties exist in the permafrost OC budget, which limits our understanding of the fate of frozen carbon in a warming world. In particular, the lack of comprehensive estimates of OC stocks across alpine permafrost means that current knowledge on this issue remains incomplete. Here, we evaluated the pool size and spatial variations of permafrost OC stock to 3 m depth on the Tibetan Plateau by combining systematic measurements from a substantial number of pedons ( i.e . 342 three‐metre‐deep cores and 177 50‐cm‐deep pits) with a machine learning technique ( i.e . support vector machine, SVM ). We also quantified uncertainties in permafrost carbon budget by conducting Monte Carlo simulations. Our results revealed that the combination of systematic measurements with the SVM model allowed spatially explicit estimates to be made. The OC density ( OC amount per unit area, OCD ) exhibited a decreasing trend from the south‐eastern to the north‐western plateau, with the exception that OCD in the swamp meadow was substantially higher than that in surrounding regions. Our results also demonstrated that Tibetan permafrost stored a large amount of OC in the top 3 m, with the median OC pool size being 15.31 Pg C (interquartile range: 13.03–17.77 Pg C). 44% of OC occurred in deep layers ( i.e . 100–300 cm), close to the proportion observed across the northern circumpolar permafrost region. The large carbon pool size together with significant permafrost thawing suggests a risk of carbon emissions and positive climate feedback across the Tibetan alpine permafrost region.

Molecular structure of glycogen in diabetic liver - Bin Deng; Mitchell A. Sullivan; Jialun Li; Xinle Tan; Chengjun Zhu; Benjamin L. Schulz; Robert G. Gilbert (Glycoconjugate Journal, 2015)

Stoichiometric shifts in surface soils over broad geographical scales: evidence from C hina's grasslands - Yuanhe Yang; Jingyun Fang; Chengjun Ji; Arindam Datta; Pin Li; Wenhong Ma; Anwar Mohammat; Haihua Shen; Huifeng Hu; Benjamin O. Knapp; Pete Smith (Global Ecology and Biogeography, 2014)
Aim The identification of stoichiometric flexibility is crucial for understanding carbon–nitrogen–phosphorus ( C – N – P ) interactions and ecosystem dynamics under a changing environment. However, current evidence of stoichiometric flexibility mainly comes from manipulation experiments, with little evidence from large‐scale observations. Location Alpine and temperate grasslands across northern C hina. Methods Using soil profiles derived from a historical national soil inventory and a contemporary regional soil survey across C hina's grasslands, we examined temporal changes in topsoil C : N : P ratios over recent decades. Results Topsoil C:N ratios of five major grassland types exhibited some flexibility but did not show significant changes over the sampling interval. Non‐significant changes in topsoil C : N ratios were observed both in alpine grasslands on the T ibetan P lateau and in temperate grasslands on the Inner Mongolian Plateau. Consistent with the relatively stable C : N ratios, the slope of the soil C – N stoichiometric relationship did not differ significantly between the two sampling periods. Soil N:P ratios in the surface layer increased significantly over the sampling interval, however, with an overall increase of 0.60 (95% confidence interval 0.58–0.62). A larger increase in soil N : P ratio was found in temperate grasslands on the I nner M ongolian P lateau than in alpine grasslands on the T ibetan P lateau. Moreover, the slope of the soil N – P stoichiometric relationship in these grassland ecosystems became steeper over the sampling interval. Main conclusions These results demonstrate the stability of topsoil C : N stoichiometry but variability in N : P stoichiometry over broad geographical scales, highlighting that soil C and N are tightly coupled, but N and P tend to be decoupled under a changing environment.

Increased topsoil carbon stock across China's forests - Yuanhe Yang; Pin Li; Jinzhi Ding; Xia Zhao; Wenhong Ma; Chengjun Ji; Jingyun Fang (Global Change Biology, 2014)
Biomass carbon accumulation in forest ecosystems is a widespread phenomenon at both regional and global scales. However, as coupled carbon–climate models predicted, a positive feedback could be triggered if accelerated soil carbon decomposition offsets enhanced vegetation growth under a warming climate. It is thus crucial to reveal whether and how soil carbon stock in forest ecosystems has changed over recent decades. However, large‐scale changes in soil carbon stock across forest ecosystems have not yet been carefully examined at both regional and global scales, which have been widely perceived as a big bottleneck in untangling carbon–climate feedback. Using newly developed database and sophisticated data mining approach, here we evaluated temporal changes in topsoil carbon stock across major forest ecosystem in China and analysed potential drivers in soil carbon dynamics over broad geographical scale. Our results indicated that topsoil carbon stock increased significantly within all of five major forest types during the period of 1980s–2000s, with an overall rate of 20.0 g C m −2 yr −1 (95% confidence interval, 14.1–25.5). The magnitude of soil carbon accumulation across coniferous forests and coniferous/broadleaved mixed forests exhibited meaningful increases with both mean annual temperature and precipitation. Moreover, soil carbon dynamics across these forest ecosystems were positively associated with clay content, with a larger amount of SOC accumulation occurring in fine‐textured soils. In contrast, changes in soil carbon stock across broadleaved forests were insensitive to either climatic or edaphic variables. Overall, these results suggest that soil carbon accumulation does not counteract vegetation carbon sequestration across China's forest ecosystems. The combination of soil carbon accumulation and vegetation carbon sequestration triggers a negative feedback to climate warming, rather than a positive feedback predicted by coupled carbon–climate models.

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Influence of limited soil on the root distribution and anchorage of Vitex negundo L. - Feng Long; Shaocai Li; Hailong Sun; Chengjun Li (Journal of Mountain Science, 2012)

Oxidative stress protection and the repair response to hydrogen peroxide in the hyperthermophilic archaeon Pyrococcus furiosus and in related species - Kari R. Strand; Chengjun Sun; Ting Li; Francis E. Jenney; Gerrit J. Schut; Michael W. W. Adams (Archives of Microbiology, 2010)

Characterization of An Avian Influenza Virus of Subtype H7N2 Isolated from Chickens in Northern China - Yanbing Li; Chengjun Li; Liling Liu; Hongwei Wang; Chuanbin Wang; Guobing Tian; Robert G. Webster; Kangzhen Yu; Hualan Chen (Virus Genes, 2006)